Inflammatory events during murine squamous cell carcinoma development - Gasparoto Thais Helena; de Oliveira Carine Ervolino; de Freitas Luisa Thomazini; Pinheiro Claudia Ramos; Ramos Rodrigo Nalio; da Silva André Luis; Garlet Gustavo Pompermaier; da Silva João Santana; Campanelli Ana Paula (BMC, 2012)
Abstract Background Squamous cell carcinoma (SCC) is one of the most common human cancers worldwide. In SCC, tumour development is accompanied by an immune response that leads to massive tumour infiltration by inflammatory cells, and consequently, local and systemic production of cytokines, chemokines and other mediators. Studies in both humans and animal models indicate that imbalances in these inflammatory mediators are associated with cancer development. Methods We used a multistage model of SCC to examine the involvement of elastase (ELA), myeloperoxidase (MPO), nitric oxide (NO), cytokines (IL-6, IL-10, IL-13, IL-17, TGF-β and TNF-α), and neutrophils and macrophages in tumour development. ELA and MPO activity and NO, IL-10, IL −17, TNF-α and TGF-β levels were increased in the precancerous microenvironment. Results ELA and MPO activity and NO, IL-10, IL −17, TNF-α and TGF-β levels were increased in the precancerous microenvironment. Significantly higher levels of IL-6 and lower levels of IL-10 were detected at 4 weeks following 7,12-Dimethylbenz(a)anthracene (DMBA) treatment. Similar levels of IL-13 were detected in the precancerous microenvironment compared with control tissue. We identified significant increases in the number of GR-1+ neutrophils and F4/80+/GR-1- infiltrating cells in tissues at 4 and 8 weeks following treatment and a higher percentage of tumour-associated macrophages (TAM) expressing both GR-1 and F4/80, an activated phenotype, at 16 weeks. We found a significant correlation between levels of IL-10, IL-17, ELA, and activated TAMs and the lesions. Additionally, neutrophil infiltrate was positively correlated with MPO and NO levels in the lesions. Conclusion Our results indicate an imbalance of inflammatory mediators in precancerous SCC caused by neutrophils and macrophages and culminating in pro-tumour local tissue alterations.